2016
DOI: 10.1128/aac.01192-16
|View full text |Cite
|
Sign up to set email alerts
|

Cefazolin and Ertapenem, a Synergistic Combination Used To Clear Persistent Staphylococcus aureus Bacteremia

Abstract: Ertapenem and cefazolin were used in combination to successfully clear refractory methicillin-susceptible Staphylococcus aureus (MSSA) bacteremia. In addition, recent work has demonstrated activity of combination therapy with beta-lactams from different classes against methicillin-resistant S. aureus (MRSA). The ertapenem-plus-cefazolin combination was evaluated for synergy in vitro and in vivo in a murine skin infection model using an index MSSA bloodstream isolate from a patient in whom persistent bacteremia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 48 publications
1
46
0
Order By: Relevance
“…Compared to MRSA, there is less clinical data on combination therapy for the treatment of persistent MSSA bacteremia, perhaps due to the improved clearance with standard of care antibiotic therapy (Kim et al, 2008;Chang et al, 2003). A recent case report described the addition of ertapenem to cefazolin after cefazolin therapy alone failed to clear blood cultures after 5 days of therapy (Sakoulas et al, 2016). The day following the addition of ertapenem, blood cultures cleared (Sakoulas et al, 2016).…”
Section: Mssamentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to MRSA, there is less clinical data on combination therapy for the treatment of persistent MSSA bacteremia, perhaps due to the improved clearance with standard of care antibiotic therapy (Kim et al, 2008;Chang et al, 2003). A recent case report described the addition of ertapenem to cefazolin after cefazolin therapy alone failed to clear blood cultures after 5 days of therapy (Sakoulas et al, 2016). The day following the addition of ertapenem, blood cultures cleared (Sakoulas et al, 2016).…”
Section: Mssamentioning
confidence: 99%
“…A recent case report described the addition of ertapenem to cefazolin after cefazolin therapy alone failed to clear blood cultures after 5 days of therapy (Sakoulas et al, 2016). The day following the addition of ertapenem, blood cultures cleared (Sakoulas et al, 2016). Additionally, there was no evidence of relapse at 90 days of follow-up (Sakoulas et al, 2016).…”
Section: Mssamentioning
confidence: 99%
“…In addition, some studies have shown the benefit of combined therapy despite the resistance of the microorganism to some antimicrobials in the scheme [24]. Synergism has also been described using DA and MIC: MIC methods against Gram-positive organisms-especially S. aureus [25][26][27]; these are likely useful methods against Gram-positive organisms. Unfortunately, for logistical reasons, we could not evaluate in vitro synergy against Gram-positive standard organisms.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some studies have shown the benefit of combined therapy despite the resistance of the microorganism to some antimicrobials in the scheme [34]. Synergism has also been described using DA and MIC:MIC methods against Gram-positive organisms -especially S. aureus [35][36][37]; these are likely useful methods against Gram-positive organisms.…”
Section: Discussionmentioning
confidence: 99%